2016
DOI: 10.1016/j.tips.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Sigma-1 Receptor as a Pluripotent Modulator in Living Systems

Abstract: The sigma-1 receptor (Sig-1R) is an endoplasmic reticulum (ER) protein resides specifically at the interface between ER and mitochondria, called the MAM, where the Sig-1R is recently reported to be involved in certain CNS diseases. In addition to being able to translocate to the plasma membrane to interact with ion channels and other receptors, the Sig-1R is found to exist at the nuclear envelope where it recruits chromatin-remodeling factors to affect the transcription of genes. As well, thorough experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
272
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(275 citation statements)
references
References 140 publications
(109 reference statements)
2
272
0
1
Order By: Relevance
“…3f). Although σ1 is an inter-organelle signaling modulator that exerts several distinct functions (e.g., ER lipid metabolisms/transports [60], and indirectly regulating the transcription of genes [4]), these data Right: Sample traces. In (a), one-way ANOVA, ****p < 0.0001.…”
Section: Cocaine Decreases Nacsh Neuronal Intrinsic Excitability In Dmentioning
confidence: 99%
See 1 more Smart Citation
“…3f). Although σ1 is an inter-organelle signaling modulator that exerts several distinct functions (e.g., ER lipid metabolisms/transports [60], and indirectly regulating the transcription of genes [4]), these data Right: Sample traces. In (a), one-way ANOVA, ****p < 0.0001.…”
Section: Cocaine Decreases Nacsh Neuronal Intrinsic Excitability In Dmentioning
confidence: 99%
“…Previous studies suggest that activation of the sigma-1 receptor (σ1), an endoplasmic reticulum (ER) chaperone [3] that regulates a variety of proteins through physical protein-protein interactions [4], contributes to addiction processes [5,6]. Consistent with this role, σ1 regulates both DA receptors signaling (DARs) via protein-protein interactions [7,8] and DA release in the striatum [9].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the structural elements and amino acids involved in the large number of reported protein-protein interactions (reviewed in [1]) is required to understand the specificity of S1R signaling. It is possible that the interface for protein-protein interactions is only accessible in the monomeric form [32,62,63], however, the surface-exposed helices A and B are attractive potential sites of interaction based on the trimeric structures.…”
Section: Where Is the Interaction Site For Protein-proteinmentioning
confidence: 99%
“…Despite its small size S1R acts to regulate the activity of a large number of cellular proteins and is itself regulated by small molecule binding [1]. The reported protein interaction partners include ion channels (both ligand and voltage gated), GPCRs, transcription factors and the endoplasmic reticulum (ER) chaperone protein BiP [2].…”
Section: Introductionmentioning
confidence: 99%
“…The sigma-1 receptor acts as a ligand-operated chaperone, which modifies the function of several receptors and channels important in neurotransmission (2), and has been the focus of intense preclinical research as a new pharmacological target for pain treatment (3,4). The role of sigma-1 receptors in neuropathic pain has been extensively studied, and it has been widely reported that sigma-1 inhibition decreases central sensitization (3), which plays a key role in this type of pain (5).…”
mentioning
confidence: 99%